The trap of time in history: The trap of time in history (Revista de História da UEG (REVHIST), 2021)
This article starts by arguing that history is a continuous effort to advance present knowledge through questions to the past and then to put the function of time in perspective. Perspectives compared to science fiction are used not so much to establish non-existent points of contact, but only as a narrative source to reposition history in its centrality: historical knowledge is important not because the past can be changed, or because it is repeated, but because of determinant importance it may have in interpreting the present. We cannot change the rise of Nazism, nor can we avoid the collapse of the Soviet Union and the transformation of the dynamics of the contemporary world, but we can, and must, question the time when things happened and, above all, how they happened.Keywords: History. Science Fiction. Time. Nazism. Soviet Union.